EVALUASI KINERJA KEUANGAN DENGAN DUPONT SYSTEM PADA SUB SEKTOR TRANSPORTASI DI BURSA EFEK INDONESIA - Dyah Shinta Kusumaningtyas; Diana Lestari; Joelianti Dwi Supraptiningsih (The Asia Pacific Journal Of Management Studies, 2025)
Financial performance evaluation is an important tool to support the right decision making and maintain company stability. This study aims to evaluate the financial performance of land transportation sub-sector companies listed on the Indonesia Stock Exchange during the period 2020 to 2024 using the DuPont System method. This method is used to analyze the company's profitability comprehensively by breaking down Return on Equity (ROE) into three main components, namely Net Profit Margin (NPM), Total Asset Turnover (TATO), and Equity Multiplier (EM). With this approach, the company can identify the main factors that influence the level of return to shareholders. This type of research is quantitative descriptive using secondary data in the form of the company's annual financial report downloaded from the official IDX website. The sample was selected using a purposive sampling technique, namely transportation companies that consistently published financial reports during the study period. The results of the analysis show that there was a significant fluctuation in financial performance during the period 2020–2024, the NPM and Total Asset Turnover (TATO) components had a significant influence on the formation of Return on Equity (ROE) during the observation period. The financial leverage factor (Equity Multiplier) also plays a role in strengthening or weakening the level of equity returns, depending on the capital structure and financial risk management of each company. This study contributes to company management and investors in understanding the important components that affect financial performance, as well as evaluation material in making strategic financial decisions.